Tuning of spinel magnesium ferrite nanoparticles with enhanced magnetic properties. Issue 68 (23rd November 2018) - Zheng, Liyun; Fang, Kan; Zhang, Meiling; Nan, Zhixian; Zhao, Lixin; Zhou, Dong; Zhu, Minggang; Li, Wei
Abstract : Monodispersed magnesium ferrite nanoparticles with enhanced magnetic properties were successfully fabricated by a simple solvothermal method without employing any templates, complex apparatus or techniques. Abstract : Monodispersed magnesium ferrite nanoparticles with enhanced magnetic properties were successfully fabricated by a simple solvothermal method without employing any templates, complex apparatus or techniques. The structure, morphology, composition, and magnetic properties of the products were tuned and characterized by X-ray powder diffraction, transmission electron microscopy, scanning electron microscopy and vibrating sample magnetometry. The results show that the reaction time and temperature have an important influence on the morphology, composition, structure and particle size of the synthesized MgFe2 O4 nanoparticles. Not only the size, size distribution, crystallization, but also the atomic ratio of Mg : Fe has a decisive effect on their magnetic properties. The MgFe2 O4 magnetic nanoparticles synthesized at 180 °C for 12 hours have excellent dispersion, narrow size distribution, good crystallinity and a Mg : Fe atomic ratio of approximately 1 : 4.53 and an average particle size of 114.3 nm, thus the highest saturation magnetization of 67.35 emu g −1 . It provides a reliable synthesis method for the better application of spinel structure magnesium ferrite nanoparticles in the future.